Characterization of the structural determinants of the ubiquitin-dependent proteasomal degradation of human hepatic tryptophan 2, 3-dioxygenase. Issue 10 (28th May 2021) - Liu, Yi; Kim, Sung-Mi; Wang, YongQiang; Karkashon, Shay; Lewis-Ballester, Ariel; Yeh, Syun-Ru; Correia, Maria Almira
Abstract : Human hepatic tryptophan 2, 3-dioxygenase (hTDO) is a homotetrameric hemoprotein. It is one of the most rapidly degraded liver proteins with a half-life ( t 1/2 ) of ∼2.3 h, relative to an average t 1/2 of ∼2–3 days for total liver protein. The molecular mechanism underlying the poor longevity of hTDO remains elusive. Previously, we showed that hTDO could be recognized and ubiquitinated by two E3 ubiquitin (Ub) ligases, gp78/AMFR and CHIP, and subsequently degraded via Ub-dependent proteasomal degradation pathway. Additionally, we identified 15 ubiquitination K-sites and demonstrated that Trp-binding to an exosite impeded its proteolytic degradation. Here, we further established autophagic-lysosomal degradation as an alternative back-up pathway for cellular hTDO degradation. In addition, with protein kinases A and C, we identified 13 phosphorylated Ser/Thr (pS/pT) sites. Mapping these pS/pT sites on the hTDO surface revealed their propinquity to acidic Asp/Glu (D/E) residues engendering negatively charged DEpSpT clusters vicinal to the ubiquitination K-sites over the entire protein surface. Through site-directed mutagenesis of positively charged patches of gp78, previously documented to interact with the DEpSpT clusters in other target proteins, we uncovered the likely role of the DEpSpT clusters in the molecular recognition of hTDO by gp78 and plausibly other E3 Ub-ligases. Furthermore, cycloheximide-chase analyses revealed the critical structural relevance of the disordered N- and C-termini not only in the Ub-ligase recognition, but also in the proteasome engagement. Together, the surface DEpSpT clusters and the N- and C-termini constitute an intrinsic bipartite degron for hTDO physiological turnover.